2020
DOI: 10.26623/themessenger.v12i2.1818
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Social Gratifications Sought and Obtained from Social Media Utilization

Abstract: <p class="Default"><em>Going by the proposition of the Uses and Gratifications Theory (UGT), people are motivated to use media by various psychological factors and for obtaining different forms of gratifications. However, as social media continue to play an essential role in shaping the sociability and bridging social connectivity and interactions among its users, therefore, this study seeks to incorporate social influence and social interactions as the social gratification sought in social media u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Raji et al's research show that social influence and interaction significantly influence the use of social media, Instagram. This study also reveals that social media is a social tool and network stimulated by social factors to achieve social goals such as getting help, support, and community involvement (Raji et al, 2020). The comparative study conducted by Phua, Jin, and Kim showed that use of Twitter had the highest social capital link, followed by Instagram, Facebook, and Snapchat, while Snapchat users had the highest social capital binding, followed by Facebook, Instagram, and Twitter (Phua et al, 2017).…”
Section: Introductionmentioning
confidence: 72%
“…Raji et al's research show that social influence and interaction significantly influence the use of social media, Instagram. This study also reveals that social media is a social tool and network stimulated by social factors to achieve social goals such as getting help, support, and community involvement (Raji et al, 2020). The comparative study conducted by Phua, Jin, and Kim showed that use of Twitter had the highest social capital link, followed by Instagram, Facebook, and Snapchat, while Snapchat users had the highest social capital binding, followed by Facebook, Instagram, and Twitter (Phua et al, 2017).…”
Section: Introductionmentioning
confidence: 72%
“…Online medical communities and support groups have sprung up to provide a platform for patients and caregivers to share experiences and seek support. For example, online platforms such as Patients Like Me allow patients to share their treatment experiences and outcomes, helping other patients understand the potential effects of different treatment regimens (Sundar & Limperos, 2013;Adetunji et al, 2020). In addition, many health applications and wearables allow individuals to monitor and track their health, thus meeting their health management needs.…”
Section: Gratifications Sought (Gs) and Gratifications Obtained (Go)mentioning
confidence: 99%
“…Social interaction also has empirically demonstrated as a significant role in motivating users and impact the usage of social media for bridging and bonding social capital in the form of attending to informational needs, community building and productive individual found social interaction has also been shown to be of great significance in the sense of media use studies. Social interaction also has been empirically demonstrated as a significant role in motivating users and impact the usage of social media for bridging and bonding social capital in the form of attending to informational needs, community building, and individual productivity [38]. With social interaction, users can exchange their views, experience, and observations which are able to build and develop relationships and connect with others.…”
Section: Social Gratificationmentioning
confidence: 99%